Bertahan di Tengah TV “Nasional” : Strategi Manajemen RBTV Melalui TV Jaringan dengan KOMPAS TV - Shabira Dwi Fadhilah; Nabila Farahnisa; Rizki Taslimatul Uyun; Nurul Fajri Hidayati (Universitas Muhammadiyah Yogyakarta, 2016)
This research was held to find out how the local television, which is RBTV, survived from “national” television by its segmentation, targeting, and positioning way. This research is important because the result is expected to be a reference for other local televisions to keep their existence and survive against many other “national” televisions. This research discusses about how RBTV’s strategy as one of local television survived from many other local televisions and “national” televisions. The research method was qualitative descriptive and for the informant was getting by purposive sampling technique. The conclusion of the research is the cooperation between KOMPAS TV and RBTV as a networked television, made mass media (especially television) escaped from media policy and goals changing and also homogenity of news and information as the results from media diversification. Other “national” television station should follow KOMPAS TV ways by networked television with RBTV to create the opportunity for local television, so they can compete with other “national” television all over Indonesia. Other local televisions are hoped to follow RBTV’s strategy through networked television with KOMPAS TV to survive from tight competition among other local television.